Diagnostic Accuracy of Total Leucocyte Count and Ultrasound in the Diagnosis of Acute Appendicitis - Shehzad Ahmed Abbasi, Ahmed Hussain Mishwani (Journal of Rawalpindi Medical College, 2012)
Background: To compare the diagnostic accuracy of Total Leucocyte Count (TLC) with Ultrasound (USG) abdomen and pelvis in diagnosis of acute appendicitis. Methods: In this cross sectional study 100 patients, with clinical diagnosis of acute appendicitis, were included. In histopathologically dignosed cases, TLC and ultrasound (USG) abdomen and pelvis findings were compared.. Chi Square test was used to find correlation. Results: The mean age was 30.17 years. The sensitivity, specificity, positive predictive and the negative predictive value of total leukocyte count was 87.5 %, 78.6%, 91.3% and 71.0%, respectively. The sensitivity, specificity, positive predictive and the negative predictive value of USG abdomen and pelvis was 44%,89.3%,91.4% and 38.5%, respectively. Conclusion: TLC has more sensitivity and diagnostic accuracy in acute appendicitis in comparison to USG abdomen and pelvis. As diagnosis in acute appendicitis is more clinical, hence it can be used alone to enhance diagnostic accuracy.